Heart-of-palm, present and future in Costa Rica - Mora-Urpí, Jorge (2002)
A brief summary of the new advances in crop technology and increased production of heart-of-palm is presented. Among the most relevant improvements are: new varieties; highest planting densities, and a new parameter to detect the optimum stage for harvesting. Those innovations have made it possible to increase production significantly. Also, new promising methods to process and commercially present heart-of-palm products have been developed, which may serve to broaden their market. The importance of increasing the knowledge on plant nutrition is pointed out, since high density planting is very demanding of fertilizer. Besides, the marketing crisis that heart-of-palm is suffering is discussed, as well as some possible measures to diminish its impact. It is considered that heart- of-palm production has a good future if research, farmers' organization and marketing are intelligently promoted by the government.